Integration of Hi-C with short and long-read genome sequencing reveals the structure of germline rearranged genomes - Robert Schöpflin; Uirá Souto Melo; Hossein Moeinzadeh; David Heller; Verena Laupert; Jakob Hertzberg; Manuel Holtgrewe; Nico Alavi; Marius-Konstantin Klever; Julius Jungnitsch; Emel Comak; Seval Türkmen; et al. (Nature Communications, 2022)
Here the authors characterize structural variations (SVs) in a cohort of individuals with complex genomic rearrangements, identifying breakpoints by employing short- and long-read genome sequencing and investigate their impact on gene expression and the three-dimensional chromatin architecture. They find breakpoints are enriched in inactive regions and can result in chromatin domain fusions.